Gerenciamento de resíduos da construção civil no município de Monteiro/PB - Pereira, Katucha Kamilla Marques (2017)
Among the serious social environmental problems facing society today is the problem of solid waste in large, medium and small cities. In Brazil, the discussion about solid waste management is not new, and has been generating several clashes and discussions with various social actors. The national solid waste policy (Law 12.305/2010) is the specific Federal Legislation relating to management and processing of waste in the national territory. Regarding civil construction waste, it was only with the CONAMA Resolution 307/2002 that guidelines, criteria and procedures for the waste management were accomplished, in order to mitigate the environmental impacts generated by the civil construction in the country. So, this research aims to study the situation of the civil construction waste in the city of Monteiro - PB. For this research, it was initially made a bibliographical and documental report about the subject. After that, four samples were chosen in the city of Monteiro, with the objectives of quantifying, classifying and identifying the main environmental impacts. For the quantification of the residues, in each sample the method of Pinto (1999) was used. For the classification of waste, it was used the CONAMA Resolution 307/2002. Concerning the identification of the environmental impacts, the Leopold Matrix (1971) was used. During the stages of the research, it was possible to identify some deficiencies in the management of construction waste in the city, such as lack of places for storage, sorting and transfer; lack of information and interest of the waste generators; irregular provision of waste; among others. At the end of the research, some alternatives were proposed for a better management and utilization of waste, more adapted to the possibilities of the city, respecting the environment and the legislation.